Sclerotherapy of venous malformations using polidocanol: effectiveness, safety, and predictors of outcomes and adverse events - Schmitt, Niclas; Lorenz, Julia; Hohenstatt, Sophia; Semmelmayer, Karl; Ruping, Fabian; Hoffmann, Jürgen; Günther, Patrick; Bendszus, Martin; Möhlenbruch, Markus Alfred; Vollherbst, Dominik (Journal of vascular and interventional radiology, 2023)
Purpose: To assess the effectiveness, safety, and predictors of outcomes and adverse events for percutaneous sclerotherapy using polidocanol for the treatment of venous malformations (VMs). Methods: A retrospective single-center analysis was performed, including patients with VMs who were treated with sclerotherapy using polidocanol between January 2011 and November 2021 at a tertiary center. Demographic characteristics, clinical data, and radiologic features were analyzed, and the influence of patient-and VM-related factors on the subjective clinical outcome and adverse events were investigated using a multivariate logistic regression analysis.Results: In total, 167 patients who received 325 treatment sessions were included in this study. Overall symptom improvement was observed in 67.5%, stable symptoms were observed in 25.0%, and worsening was reported in 7.5% (clinical follow-up, 1.04 +/- 1.67 years). The total adverse event rate was 10.2%, with an overall rate of 4.2% for permanent adverse events within the cohort. In multivariate analysis, the clinical outcome was worse in children (P = .01; 57.1% symptom improvement in children [age, <18 years] and 79.7% in adults), and adverse events were more frequently observed after the treatment of VMs located at the extremities (P < .01; 8.4% for VMs of the extremities and 1.2% for VMs in other locations).Conclusions: Sclerotherapy using polidocanol can be an effective treatment option for VMs with an acceptable safety profile. However, it can be less effective in children, and adverse events can be more frequently expected for VMs of the extremities.